Highly Scalable, Sensitive and Ultraflexible Graphene‐Based Wearable E‐Textiles Sensor for Bio‐Signal Detection. Issue 1 (26th October 2022) - Tan, Sirui; Islam, Md Rashedul; Li, Huixuan; Fernando, Anura; Afroj, Shaila; Karim, Nazmul
Abstract: Graphene‐based wearable electronic textiles (e‐textiles) show promise for next‐generation personalized healthcare applications due to their non‐invasive nature. However, the poor performance, less comfort, and higher material cost limit their wide applications. Here a simple and scalable production method of producing graphene‐based electro‐conductive yarn that is further embroidered to realize piezoresistive sensors is reported. The multilayer structures improved the conductivity of the piezoresistive sensors, exhibiting good sensitivity with high response and recovery speed. Additionally, the potential applications of such wearable, ultraflexible and machine‐washable piezoresistive sensors as pressure and breathing sensors are demonstrated. This will be an important step toward realizing multifunctional applications of wearable e‐textiles for next‐generation personalized healthcare applications. Abstract : A simple and scalable production method of producing graphene‐based electro‐conductive yarn that is further embroidered to realize piezoresistive sensors is reported. The multilayer structures improved the conductivity of the piezoresistive sensors, exhibiting good sensitivity with high response and recovery speed. Additionally, the potential applications of such wearable, ultraflexible and machine‐washable piezoresistive sensors as pressure and breathing sensors are demonstrated.